Frequency and Correlation of Body Mass Index and Waist-Hip Ratio with Fasting Glycemia and Blood Pressure in High School Students from Mexico - Lourdes Adriana Medina-Gaona; Nallely Enríquez-Sánchez; Carla Elizabeth Mejía- Ramírez; Nathalia de Jesús Orueta-Mondragón; Heriberto Medina-Franco; Yareri Sandoval-Morales; Tanya Plett-Torres (International Journal of Medical Students, 2018)
Background: Overweight/obesity is a global public health problem in adolescents. Its frequency is increasing as similar to diabetes, hypertension, health expenses, and poor quality of life. Thus, detecting overweight/obesity early in life promises a positive impact on the world’s health.